Pharmacotherapy for AMD: state-of-the-art - I.A. Koroleva; A.A. Gvetadze; T.B. Romanova (РМЖ "Клиническая офтальмология")
The article discusses the evolution of the treatment for a socially important disease, age-related macular degeneration (AMD). Data on earlier and recent treatment for “wet” AMD as well as promising trends in the development of novel medications are addressed.  It was established that AMD is one of the most common causes of low vision in people over 50 years in developed countries. An estimated 30 to 50 million patients worldwide suffer from this disease. “Wet” AMD is responsible for 90% of visual impairment or blindness due to AMD. About 500,000 of new “wet” AMD cases are diagnosed every year worldwide. Agents which prevent neovascularization by inhibiting vascular endothelial growth factor (VEGF) are currently used to manage this rapidly progressing type of AMD. It was demonstrated that VEGF inhibiting prevents the development of choroidal neovascular membrane, reduces the sizes of pre-existing membrane, and decreases vascular leakage from new vessels. Ranibizumab and aflibercept (Eylea) are the most well-studied and commonly used agents.  Keywords: age-related macular degeneration, AMD, choroidal neovascular membrane, intravitreal injection, VEGF, ranibizumab, aflibercept, Eylea.  For citation: Koroleva I.A., Gvetadze A.A., Romanova T.B. Pharmacotherapy for AMD: state-of-the-art. Russian Journal of Clinical Ophthalmology. 2019;19(2):105–109.  About the authors: 1Irina A. Koroleva — MD, PhD, ophthalmologist, ORCID iD 0000-0003-1679-5701; 2Anna A. Gvetadze — MD, PhD, ophthalmologist, ORCID iD 0000-0003-4535-2694; 3Tatiana B. Romanova — MD, PhD, Associate Professor of the Department of Ophthalmology, ORCID iD 0000-0002-3865-2691. 1City Clinical Hospital No. 15. 23, Veshnyakovskaya str., Moscow, 111539, Russian Federation. 2LLC “Clinic “Sphere”. 10, Starokachalovskaya str., Moscow, 117628, Russian Federation. 3Pirogov Russian National Research Medical University. 1, Ostrovityanova str., Moscow, 117997, Russian Federation. Contact information: Irina A. Koroleva, e-mail: tvoya-z@ya.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 14.04.2019.